Approach to Minimize the Necessary of Technical Resources for Metrology of Data Storage in Smart Grid - Kravtsov, H. A. (Інститут проблем реєстрації інформації НАН України, 2013)
It is described an approach on modeling the distribution of metering points in the domain of energy which has been reduced to normalized additive function of distribution based on two-dimensional normal distribution. The goal of modeling is to reduce the technical resources (disk space) for metrology of data storage with a digital signature. Fig.: 5. Refs: 4 titles.